2019
DOI: 10.1111/jvim.15676
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between tracheobronchoscopic score and bronchoalveolar lavage red blood cell numbers in the diagnosis of exercise‐induced pulmonary hemorrhage in horses

Abstract: Background: Exercise-induced pulmonary hemorrhage (EIPH) is diagnosed and its severity assessed by post-exercise tracheobronchoscopy, and enumeration of bronchoalveolar lavage fluid red blood cells (BALFRBC). Minimal information is available regarding the relationship of tracheobronchoscopy score to BALFRBC number.Objective: Evaluate the relationship between BALFRBC number and tracheobronchoscopy scores and determine their diagnostic sensitivities.Animals: Nine sedentary horses, 21 fit Thoroughbreds, 129 Barre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 26 publications
0
23
0
3
Order By: Relevance
“…This is not unexpected as it has been well established that most horses undergoing strenuous exercise have some degree of bleeding (Erickson, 1994). Furthermore, it has been suggested that horses ultimately diagnosed with EIPH using methods, such as quantitation of RBCs in BAL fluid, do not necessarily have signs of hemorrhage on endoscopic examination (Hinchcliff, McKeever, & Muir, 1991; Lester et al., 1999; Sanchez, Kogan, Gold, Sellon, & Bayly, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This is not unexpected as it has been well established that most horses undergoing strenuous exercise have some degree of bleeding (Erickson, 1994). Furthermore, it has been suggested that horses ultimately diagnosed with EIPH using methods, such as quantitation of RBCs in BAL fluid, do not necessarily have signs of hemorrhage on endoscopic examination (Hinchcliff, McKeever, & Muir, 1991; Lester et al., 1999; Sanchez, Kogan, Gold, Sellon, & Bayly, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…15 This method is relatively easy to perform and seems to have a very high specificity. 18 However, sensitivity was estimated to be only 59% (many false negative diagnoses) when compared to RBC content in respiratory fluid cells. 18 Therefore, it has been proposed that a lack of tracheobronchoscopic evidence of blood cannot be used to rule out EIPH.…”
Section: Introductionmentioning
confidence: 99%
“…30 As compared to tracheobronchoscopy, those tests are generally assigned a higher sensitivity and many authors have recommend these as the best available diagnostic tests. 13,16,18,28,33,34 Whereas RBC counts can only be used to diagnose a recent EIPH episode within a few hours to days, increased hemosiderin content in alveolar macrophages (i.e. hemosiderophages) may reveal less recent EIPH episodes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations